1984
DOI: 10.1111/j.1365-2621.1984.tb13732.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Postmortem Storage on Muscle Protein Degradation: Analysis by SDS-Polyacrylamide Gel Electrophoresis

Abstract: Changes in myofibrillar proteins of bovine longissimus and semitendinosus muscles were examined during 14 days of postmortem storage at 2°C by SDS-Polyacrylamide gel electrophoresis. Major changes in both muscles were: (1) appearance of a 95,000-dalton component;(2) gradual disappearance of troponin-T and gradual appearance of a 30,000-dalton component; (3) gradual increase in intensity of a protein around 55,000-daltons; and (4) gradual appearance of a 110,OOOdalton component. With the exception of the 95,000… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
30
0
1

Year Published

1994
1994
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(35 citation statements)
references
References 8 publications
4
30
0
1
Order By: Relevance
“…This further implies that the proteolysis in LA samples with lower pH could be more extensive than that in CON and AA samples. This 95 kDa polypeptide was ®rst identi®ed in post-mortem bovine muscles by Koohmaraie et al 27 and consistently noted in animal muscles from various species afterwards. 26,28,29 The origin of the 95 kDa polypeptide remains unclear, though Koohmaraie et al 27 have suggested that it may originate from any of the myo®brillar proteins which have subunit molecular weights larger than 95 kDa.…”
Section: Resultsmentioning
confidence: 95%
“…This further implies that the proteolysis in LA samples with lower pH could be more extensive than that in CON and AA samples. This 95 kDa polypeptide was ®rst identi®ed in post-mortem bovine muscles by Koohmaraie et al 27 and consistently noted in animal muscles from various species afterwards. 26,28,29 The origin of the 95 kDa polypeptide remains unclear, though Koohmaraie et al 27 have suggested that it may originate from any of the myo®brillar proteins which have subunit molecular weights larger than 95 kDa.…”
Section: Resultsmentioning
confidence: 95%
“…Further, Stadtman (2006) reported that increasing age increased the susceptibility of muscle cells to oxidizing agents in small animals and humans because agerelated loss in redox potential could predispose postmortem muscles to higher rates of oxidation in old cows. A limited number of studies have been conducted to investigate the possible effects of animal age on the postmortem progression of proteolysis in relation to meat tenderness (Huff-Lonergan et al, 1995; Koohmaraie et al, 1984;Parrish, 1981). These studies showed a reduced rate of post-mortem myofibrillar protein degradation in muscle from physiologically mature (E maturity) cattle compared to muscle from young (A maturity) carcasses and the variability in beef tenderness resulted from the different physiological ages of cattle.…”
Section: Introductionmentioning
confidence: 99%
“…The amount and activity of enzymes in the glycolysis pathway, and level of muscle glycogen at slaughter are conditioned by the range of glycolytic changes, which, in turn, influence the decrease in meat pH levels and activation of proteolytic enzymes. As a result of the enzyme activity in meat, new components with molecular weights of 110, 95, and 55 kDa as well as molecular weights less than 30 kDa appear in meat and they are indicators of the degree of proteolysis of myofibrillar proteins [1][2][3][4]. Generation of a protein/polypeptide profile determines many traits that influence the technological (water capacity, color intensity, color homogeneity, stability, losses in cooking, and losses in processes) and sensory qualities (appearance, tenderness, juiciness, flavor, and odor) of pork meat.…”
Section: Introductionmentioning
confidence: 99%